Avaliação da satisfação de famílias vinculadas ao Programa Criança Feliz - Bráz, Gabriela Maria (2020)
Children from zero to six years old, period considered early childhood in Brazil, are equivalent to 11% of the Brazilian population, being the target of various policies, investments and research on development and care models. In this sense, the Happy Child Program (PCF) emerges as a Federal Government policy for families with children between zero and six years old to be oriented towards integral child development. Many of these actions still consider the families of these children as individuals who still need to learn how to handle situations involving care and development. This study aims to investigate the satisfaction of families with the intervention received within the PCF in a municipality in the region of São Carlos - SP, as well as to analyze how the families participating in the Program see their personal-social network and the service network to which they live. are integrated. This is a descriptive and exploratory study with a qualitative approach, built and developed with the PCF teams of the municipality. The data collection instruments used were an adaptation of the “Family Satisfaction Assessment” Survey and the “Network Map”, and the above-mentioned instruments were applied to the families participating in the PCF. Data collected in the survey were analyzed using descriptive statistics techniques. For the Network Map, a General Network Map of the participants was built and its qualitative analysis was performed by quadrants according to their structural characteristics. The results obtained showed, in the general framework of the Satisfaction Assessment Survey, a frequency of low satisfaction of 45%. Regarding the Network Map, it was evidenced that the personal-social network within the “Family” quadrant is the largest, also showing that the services that were intermediated by the PCF represent only 22.2% of the total services that were cited by the families. It is concluded that low levels of satisfaction in some specific areas of the Survey demonstrate deficits according to what is predicted by the Happy Child Program guide material itself. In addition, it reflects on the importance of directing attention to issues of intersectoriality, as it is conceived as a characterizing component of the Program.